DIKSI PADA TEKS NARASI SISWA SEKOLAH DASAR - Madu, Fransiska Jaiman (STKIP Santu Paulus Ruteng, 2015)
Abstract: Diction on Narrative Text Elementary School Students. This study aimed to describe the diction in the text narrative fourth grade students based on three conditions, namely,(1) accuracy requirements (2) predominance requirement (3) and the meaning of rules. This research is qualitative approach and descriptive methods , used 12 subjects. Through assignment technique with predetermined topics. Researchers provided 6 topics narrative text (stories). The number of overall narrative text that was produced as many as 72 student text. The result diction analysis on narrative text students demonstrate, based on the accuracy requirements, the data encountered sinonym diction, active diction, passive diction, conjunctions, preposition, which is not the right word because it does not fit the context of the sentence, incorrect word usage as a result of the particles and incorrect word usage as a result of affixation. In addition, correct data relation to synonyms, active diction, passive diction, conjunctions, prepositions, a common word, special words, a change of meaning include : expansion of the meaning, a narrowing of meaning, synesthesia, and ameliorative. Based on the predominance requirement are common diction and diction was not common in the narrative text students. Furthermore, based on the terms of diction rules meaning there was not correct denotative meaning. Then, the use connotative include positive diction and negative connotative. Keywords: narrative text, diction, accuracy, prevalence, meaning rule Abstrak: Diksi Pada Teks Narasi Siswa SD. Penelitian ini bertujuan untuk mendeskripsikan diksi pada teks narasi siswa kelas IV yang didasari pada tiga syarat yaitu, (1) syarat ketepatan, (2) syarat kelaziman, dan (3) syarat kaidah makna. Penelitian ini menggunakan pendekatan kualitatif dan metode deskriptif. Teknik yang digunakan adalah teknik penugasan dan terdapat 12 subjek penelitian. Melalui teknik penugasan siswa menyusun teks narasi berdasarkan topik yang telah ditentukan (6 topik). Jumlah teks narasi secara keseluruhan yang dihasilkan siswa sebanyak 72 teks. Hasill analisis diksi pada teks narasi siswa menunjukkan, berdasarkan syarat ketepatan, terdapat data ketidaktepatan pada sinonim, diksi aktif, pasif, kata hubung, kata depan, kata yang tidak sesuai konteks kalimat, kata yang tidak tepat akibat salah penggunaan partikel dan kata yang tidak tepat akibat salah penggunaan afiksasi. Selain itu, terdapat data yang tepat berkaitan dengan sinonim, diksi aktif, pasif, kata hubung, kata depan, kata umum, kata khusus, perubahan makna mencakup: perluasan arti, penyempitan arti, sinestesia, dan ameliorasi. Berdasarkan syarat kelaziman terdapat diksi yang lazim tetapi tidak terdapat diksi yang tidak lazim. Selanjutnya, berdasarkan syarat kaidah makna terdapat diksi yang bermakna denotatif yang tidak tepat. Kemudian, penggunaan diksi konotatif yang mencakup konotatif positif dan konotatif negatif. Kata kunci: teks narasi, diksi, ketepatan, kelaziman, kaidah makna